2012
DOI: 10.1371/journal.pone.0042372
|View full text |Cite
|
Sign up to set email alerts
|

Early-to-Mid Gestation Fetal Testosterone Increases Right Hand 2D∶4D Finger Length Ratio in Polycystic Ovary Syndrome-Like Monkeys

Abstract: A smaller length ratio for the second relative to the fourth finger (2D∶4D) is repeatedly associated with fetal male-typical testosterone (T) and is implicated as a biomarker for a variety of traits and susceptibility to a number of diseases, but no experimental human studies have been performed. The present study utilizes the rhesus monkey, a close relative of humans, and employs discrete gestational exposure of female monkeys to fetal male-typical T levels for 15–35 days during early-to-mid (40–76 days; n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(93 citation statements)
references
References 124 publications
4
88
0
Order By: Relevance
“…The weaker relationship between the 2D:4D ratio of the left hand compared with that of the right hand with any of the parameters measured may be explained, at least partially, by findings from other studies suggesting differences between the left and right hands regarding apparent fetal androgen exposure. There are reports in the literature illustrating that the relationship of fetal androgen exposure to the 2D:4D ratio is stronger between digit measurements of the right hand compared to the left [9,13]. The stronger association of the right hand 2D:4D ratio with various traits assumed to be impacted by in utero androgen exposure is in line with previous findings where masculinizing traits are found to be more pronounced on the right side of the body [13].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The weaker relationship between the 2D:4D ratio of the left hand compared with that of the right hand with any of the parameters measured may be explained, at least partially, by findings from other studies suggesting differences between the left and right hands regarding apparent fetal androgen exposure. There are reports in the literature illustrating that the relationship of fetal androgen exposure to the 2D:4D ratio is stronger between digit measurements of the right hand compared to the left [9,13]. The stronger association of the right hand 2D:4D ratio with various traits assumed to be impacted by in utero androgen exposure is in line with previous findings where masculinizing traits are found to be more pronounced on the right side of the body [13].…”
Section: Discussionsupporting
confidence: 86%
“…PCOS is the number one cause of infertility in premenopausal women, and frequently women with PCOS have metabolic diseases such as hypertension and insulin resistance [1]. Interestingly, treatment of various animals prenatally with testosterone produces the metabolic as well as reproductive disorders associated with PCOS [2][3][4][5][6][7][8][9]. The metabolic defects associated with prenatal androgen exposure are not limited to females, but are also seen in males [2,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Further, it is uncertain when in gestation digit ratio is established. Experimental data has indicated that supraphysiological androgen exposure in early, but not late gestation, increased the length of the second digit and had no effect on the fourth digit in female rhesus monkeys, thereby resulting in a less male-like ratio [1]. Conversely, in female mice, in utero exposure to supraphysiological concentrations of the potent androgen dihydrotestosterone or a blocking estrogen action increased the length of the fourth digit, but had no effect on the second digit, resulting in a more male-like digit ratio pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Manno30 has shown that the correlation between prenatal androgen level and digit length in mice is more complex to assess and to explain than a direct relation, though other studies have shown the opposite 15. In monkeys, for instance, the results observed in subjects exposed to early testosterone levels during pregnancy are more nuanced than the results in mice 31. They do however confirm the influence of sex hormones on digit growth and genital development in primates.…”
Section: Discussionmentioning
confidence: 97%